(untitled) (Konferensiyalar | Conferences, 2024)
The society we live in is always changing. And knowledge is constantly updated, especially in the issues of modern higher education. The creation of innovative ideas and technologies is growing. Even throughout the world, the skills of the educational systems, especially at the university level, are being formed, updated, and improved through the exchange of experiences between the leading countries of the world and other countries. A number of changes and updates are being introduced not only at the university level but also in the preschool and school education systems. Basic knowledge is basic knowledge, and if good education is given at the beginning, young people will acquire knowledge in this way in higher education systems. The reason why more attention is paid to skills at the university level is that it is necessary for a person to develop, progress, and mature as a necessary member of society. Of course, this is very necessary for the state and for the innovative pedagogy that is being updated. Taking this into account, the main goal of the article is the development of modern forms of innovative pedagogy at the university level.